Carvone modulates in vitro and in vivo the kinetic behaviour and efficacy of abamectin - Miró, María Victoria (2020)
The search of novel strategies to control gastrointestinal nematodes in ruminants is a concern considering the increasing of anthelmintic resistance. Bioactive phytochemicals may contribute to improve parasite control by enhancing the effect of existing anthelmintic drugs. This work assessed the in-vitro and in-vivo pharmacological interaction and the in-vivo efficacy of abamectin (ABM) combined with the plant-derived compounds carvone (CNE), in lambs naturally infected with resistant gastrointestinal nematodes.